SMK Gudang Rasau student creates I-Bracealert to prevent dozing off in class, wins gold and Special Award at CITREX 2025 - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 19 June 2025 – To address the issue of students frequently falling asleep during lessons and examinations, a group of young researchers from Sekolah Menengah Kebangsaan (SMK) Gudang Rasau Kuantan, Husna Aqilah Mohd Zaidi, Nurkyreen Khairil Shuhaidi, and Iris Marissa Mazman, developed I-Bracealert, which won a gold medal and Special Award at the Creation, Innovation, Technology and Research Exposition (CITREX) 2025 held from 18 to 19 June 2025 at the Sports Complex Hall, UMPSA Gambang Campus.